FAKTOR-FAKTOR YANG MEMPENGARUHI PEMBERIAN SUSU FORMULA PADA BAYI BARU LAHIR DI WILAYAH KERJA UPT PUSKESMAS MARE - Sulfianti (Jurnal Suara Kesehatan, 2021)
Abstract. Normal newborns are babies born with a weight between 2500-4000 grams, full term, born crying, and no severe congenital defects. Breastmilk is an ideal food for babies, especially in the first months. Exclusive breastfeeding is recommended for a minimum period of six months. Formula milk (cow's milk) does not contain DHA like breast milk so it cannot help increase the intelligence of babies. There are more than 100 types of nutrients found in breast milk, including DHA, tauri, and spingomyelin which are not found in cow's milk.This study was to determine the factors that influence formula feeding in newborns. This study was an analytical survey using a cross sectional study design. The subjects in this study were 30 people. The independent variables in this study are education, work, knowledge, and socio-economy. The dependent variable is formula feeding.from 30 respondents in this study, the number of mothers who gave formula milk to newborns was 17 people. It is found that there is an effect of education by giving formula milk using chi square analysis with a value of p = 0.15 (α ≤ 0.05), which means it is significant. It was found that there was an effect of knowledge by giving formula milk using chi square analysis with a value of p = 0.08 (α ≤ 0.05) which means significant. From the results of statistical tests, it was found that there was a socio-economic effect by giving formula milk using chi square analysis with a value of p = 0.21 (α ≤ 0.05) which means significan. Keywords : formula milk, newborn baby